2020
DOI: 10.1016/j.gie.2019.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of liquid-based cytology with conventional smear cytology for EUS-guided FNA of solid pancreatic masses: a prospective randomized noninferiority study

Abstract: Background and Aims: There are limited data on the efficacy of liquid-based cytology (LBC) for EUS-guided FNA specimens. We aimed to evaluate the diagnostic efficacy of LBC for solid pancreatic neoplasms compared with conventional smears (CSs).Methods: In this randomized, crossover, noninferiority trial, we randomly assigned (1:1) patients with suspected pancreatic cancer to the LBC group or the CS group. Aspirates from the first needle pass were processed by one method, aspirates from the second pass by the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 32 publications
(48 reference statements)
0
45
0
Order By: Relevance
“…From an initial pool of 756 studies, 454 records were screened and 48 full-length articles were assessed. A total of nine studies (including 1308 patients) were included in the final analysis 18 32 33 34 35 36 37 38 39 . None of the included studies used ROSE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From an initial pool of 756 studies, 454 records were screened and 48 full-length articles were assessed. A total of nine studies (including 1308 patients) were included in the final analysis 18 32 33 34 35 36 37 38 39 . None of the included studies used ROSE.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies originated in Korea, two in China, and one each from the Netherlands, the United States, and Japan. Three studies used the precipitation-based technique of LBC 32 33 34 whereas six used the filtration-based technique (five studies used ThinPrep ® and one used CellPrep ® 18 ). The schematic diagram demonstrating our study selection is shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LBC can eliminate unnecessary background inflammatory and blood cells to increase diagnostic accuracy. Recent studies reported that LBC showed similar results to conventional smear for diagnosis of pancreatic masses [3,4]. The use of LBC may be limited for mucinous neoplasms because mucin is more dilute and scant on LBC preparations.…”
Section: Different Preparation Methodsmentioning
confidence: 99%
“…signi cantly greater than those of CS (P < 0.0001), and the sensitivity and accuracy of both CS and TCT were signi cantly greater than those of TCT or CS based on the three cases (P < 0.0001). [15,16]. In LBC, the cytological features of malignancy are retained and enhanced in a smaller screening area, which enhances accuracy in detection of malignant cells.…”
Section: Diagnostic Yield Of Us-fnamentioning
confidence: 99%